The Role of the Oil Component in Promoting Economic Growth in Norway 2010-2020 (Tikrit Journal For Political Science, 2025)
The objective of this research is to explore the Norwegian experience in the oil industry, as it is considered one of the most successful global experiences. The study used the historical method and focused on Norway and its economy. The research analyzed the relationship between oil revenues and economic growth in Norway during the period 2010-2020. Since the dawn of the 1960s, when the Norwegian oil industry was born, Norway transformed from an oil-importing country to an oil-exporting one. Norway's production has stabilized at around two million barrels per day. The oil industry has played a major role in developing the welfare state in Norway today. With proven reserves of 6.6 billion barrels of crude oil, Norway relies on the production and export of crude oil. Oil exports accounted for more than half of Norway's total exports, while the oil and natural gas sector contributed approximately 20% of the GDP. Thanks to the Norwegian government's policies in utilizing oil revenues, the country has avoided the shocks faced by the oil market. The research concluded that the relationship between economic growth and oil revenues during this period was a strong positive relationship.
Keywords: Economic growth, oil revenues, Norwegian economy